THE DETERMINATIONS OF TOTAL ACIDS IN RED WINE - B. Rajković, M.; D. Stanojević, D.; D. Novaković, I.; V. Tošković, D.; M. Sudar, M. (Journal of Engineering & Processing Management, 2009)
The amount of total acids in must is in most number of cases between 5 and 8 g/dm3 . Wines in general possess a little fewer acids than must, by Regulation the least acidity, expressed as tartaric acid is for all kinds of wine 4.5 g/dm3 , because a part of tartaric acids sediments as salt (tartar) in the process of the alcohol fermentation. For wines that possess less than 4 g/dm3 of total acids there is a doubt are they of natural background. Because of that the aim of this work was determination of total acids in diferent sorts of red wines and to determinate their background using gained data. For determinating total acids in white wine neutralization method was used. As potentiometric titration for pH 7.00 is precise and accurate method and values of content of total acids in wine, exppressed by tartaric acid, are given by these results. The analisys of differential potentiometric curves indicates that these curves can give the answer to the questions: are there inorganic supstances, amino groups and phenols present in analised samples.